2018
DOI: 10.1155/2018/8082502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal (Mn, Ti) Doping on NCA Cathode Materials for Lithium Ion Batteries

Abstract: NCA (LiNi 0.85 Co 0.10 Al 0.05−x M x O 2 , M=Mn or Ti, < 0.01) cathode materials are prepared by a hydrothermal reaction at 170 ∘ C and doped with Mn and Ti to improve their electrochemical properties. The crystalline phases and morphologies of various NCA cathode materials are characterized by XRD, FE-SEM, and particle size distribution analysis. The CV, EIS, and galvanostatic charge/discharge test are employed to determine the electrochemical properties of the cathode materials. Mn and Ti doping resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 38 publications
(37 reference statements)
3
19
0
1
Order By: Relevance
“…As reported in the previous work, the cation mixing caused by a similar radius of Li + and Ni 2+ ions would inhibit the transfer of Li ions in the Li layer of the NCM cathode particles, which leads to non-negligible negative impacts on the electrochemical performance, especially the rate capability and cycling stability. 50,51 The value of cation mixing degree for the 0.2ANCM cathode sample is the lowest, which suggests that the 0.2ANCM cathode sample would display better performance in the latter electrochemical test than other prepared cathode electrodes.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…As reported in the previous work, the cation mixing caused by a similar radius of Li + and Ni 2+ ions would inhibit the transfer of Li ions in the Li layer of the NCM cathode particles, which leads to non-negligible negative impacts on the electrochemical performance, especially the rate capability and cycling stability. 50,51 The value of cation mixing degree for the 0.2ANCM cathode sample is the lowest, which suggests that the 0.2ANCM cathode sample would display better performance in the latter electrochemical test than other prepared cathode electrodes.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…This expands the interlayer distance, allowing for easier Li + movement as well as reducing the severity of Li/Ni mixing. 210,232 Liu et al have found the concentration of 1% atom to be optimal. Ti may also act as ''pillar'' ions, supporting the structure through repeated lithiation/delithiation and preventing collapse.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…Mn and Ti have atomic radii similar to Ni and coordinate with oxygen to replace transition metal atoms in octahedral interstitial sites. Wan et al [82] prepared a LiNi 0.85 Co 0.1 Al 0.05 O 2 (NCA) cathode material by hydrothermal reaction and doping with the transition metals Mn and Ti, respectively. In the voltage range of 3.0-4.3 V, the initial discharge specific capacity of NCA-Ti and NCA-Mn was 179.6 mAh g -1 and 171.4 mAh g -1 , respectively, which was higher than that of undoped NCA (156.5 mAh g -1 ).…”
Section: Doping and Functionalizationmentioning
confidence: 99%